2017
DOI: 10.1111/dme.13383
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐existing diabetes is a risk factor for increased rates of cellular rejection after kidney transplantation: an observational cohort study

Abstract: Kidney allograft recipients with diabetes at transplantation should be counselled regarding their increased risk of cellular rejection but reassured regarding the lack of any adverse impact on short-to-medium term allograft function or survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…On the other hand, Baek et al [28] reported that there were no significant changes in the rates of rejection between diabetic and non-diabetic recipients. Some authors suggested that patients with diabetes were rendered susceptible to cellular rejection because of their significant risk of exacerbation of glycemic control after transplantation and that strict glycemic control might be important [4, 28]. In this study, glycemic control was relatively good because of the less than 7.0% HbA1c levels, which the Japan Diabetes Society recommends in order to avoid diabetic complications.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…On the other hand, Baek et al [28] reported that there were no significant changes in the rates of rejection between diabetic and non-diabetic recipients. Some authors suggested that patients with diabetes were rendered susceptible to cellular rejection because of their significant risk of exacerbation of glycemic control after transplantation and that strict glycemic control might be important [4, 28]. In this study, glycemic control was relatively good because of the less than 7.0% HbA1c levels, which the Japan Diabetes Society recommends in order to avoid diabetic complications.…”
Section: Discussionmentioning
confidence: 75%
“…Previous reports have shown that hyperglycemia might be associated with an increased risk of acute allograft rejection in transplant recipients with diabetes [4]. Meanwhile, Clatworthy et al [26] suggested that B cell-related cytokines caused by rituximab administration were associated with higher rates of acute cellular rejection in rituximab-treated patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 La evidencia para eventos negativos relacionados al cambio por sirolimus está bien descrita. 42 Los artículos vinculan un incremento de riesgo de rechazo predominantemente celular en pacientes con DM pre o PTDM 43,44 y no se sabe si es una asociación bilateral, es decir, que más rechazo conlleve a incremento de esteroides o inversamente más DM2 o riesgo de DMPT predispone a esquemas de reducción rápida de esteroides que incrementan el riesgo de rechazo. 34,38,39 La literatura es controversial.…”
Section: Este Documento Es Elaborado Por Medigraphicunclassified